The evaluation of pilots performance and mental workload by eye movement - Li, Wen-Chin; Chiu, Fa-Chung; Wu, Ka-Jay (Cranfield University, 2012)
Pilots make important decisions often using ambiguous information, while under stresses and with very little time. During flight operations detecting the warning light of system failure is a task with real-world application relates to measurement of pilot's performance and eye movement. The demand for a pilot’s visual and situational awareness in multiple tasks can be detrimental during pilots’ mental overload conditions. The purpose of this research is to evaluate the relationship between pilot’s mental workload and operational performance by eye tracking. Collecting eye movement data during flight operations in a virtual reality of flight simulator provided useful information to analysis participants’ cognitive processes. There were 36 pilots participated in this research, the experience of flight hours between 320 and 2,920, the range of age between 26 and 51 years old. The apparatus included Applied Science Laboratories (ASL) eye tracking, IDF flight simulator and NASA_TLX for data collection. The results show that pilots with high SA detecting hydraulic malfunction have shorter total fixation duration on Air Speed Indicator and longer total fixation duration on Altitude Indicator, Vertical Speed Indicator, Right multi-display and Left multi-display compared with pilots without detecting the signal of hydraulic malfunction. Pilots’ total fixation time on Integration Control Panel, Altitude Indicator, Attitude Indicator and Right Multi-display, and pilots’ subjective rating on NASA-TLX effort dimension for the mission of close pattern have significant relationship with pilots’ performance on the operational time for completing the tactic mission. Experienced pilots operate aircraft familiar with monitoring Airspeed Indicator and kinetic maneuvering result in less fuel consumption. This study could provide guidelines for future training design to reduce pilots mental workload and improve situational awareness for enhancing flight safety.
Keywords: Eye Movements, Human Errors, Mental Workload, Situational Awareness